2018
DOI: 10.1182/blood-2018-99-115200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Myeloma Cell and Soluble B-Cell Maturation Antigen (BCMA) in Relapsed and Refractory Multiple Myeloma Patients Treated with GSK2857916 in BMA117159

Abstract: Introduction: B-cell maturation antigen (BCMA) is a cell surface receptor that is widely expressed on multiple myeloma (MM) cells. GSK2857916 is a humanized Fc enhanced IgG1 anti-BCMA antibody conjugated to the microtubule inhibitor monomethyl auristatin-F (MMAF). Safety and clinical efficacy of a Q3W GSK2857916 dosing schedule were assessed in relapsed/refractory MM subjects in the first time in human trial BMA117159. In the dose escalation phase, 38 subjects were treated with doses from 0.03 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A remarkable decrease in sBCMA level was observed in patients with good responses to BCMAtargeted immunotherapy, suggesting sBCMA as a new biomarker for monitoring response to MM therapy [63]. Interestingly, unlike sBCMA, many studies have shown that the level of cell-surface BCMA does not seem to affect the response to BCMA-targeted immunotherapy [64]. It is quite possible that the varied levels of surface BCMA in MM patients are simply the result of the shedding variations of the membrane BCMA.…”
Section: Soluble Bcma (Sbcma)mentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable decrease in sBCMA level was observed in patients with good responses to BCMAtargeted immunotherapy, suggesting sBCMA as a new biomarker for monitoring response to MM therapy [63]. Interestingly, unlike sBCMA, many studies have shown that the level of cell-surface BCMA does not seem to affect the response to BCMA-targeted immunotherapy [64]. It is quite possible that the varied levels of surface BCMA in MM patients are simply the result of the shedding variations of the membrane BCMA.…”
Section: Soluble Bcma (Sbcma)mentioning
confidence: 99%
“…However, non-responders were found to have a higher baseline level of circulating sBCMA than the responders. A higher dose of GSK2857916 (≥ 1.92 mg/kg) was required to bind a large fraction of sBCMA [64]. A multicenter randomized phase 2 trial (DREAMM-2, NCT03525678) is further evaluating the safety and efficacy of belantamab mafodotin (BLMF) in R/R MM [70].…”
Section: Belantamab Mafodotin (Gsk2857916; Blenrep; Glaxosmithkline mentioning
confidence: 99%
“…Although BCMA is a validated therapeutic target in MM, sBCMA may be a significant covariate affecting the pharmacokinetics (PK) of some BCMA-targeted therapies, such as belantamab mafodotin, by reducing binding of these agents to membrane-bound BCMA and, in turn, reducing their efficacy. 2 It is unclear if this effect will broadly alter the efficacy of all BCMA-targeting agents. Additionally, it is unclear whether sBCMA levels are associated with baseline tumor burden and treatment response independent of therapeutic target.…”
mentioning
confidence: 99%
“…In contrast to sBCMA, numerous investigations have demonstrated that the amount of BCMA on the cell surface appears not to influence the reaction to BCMA-targeted therapy [64]. It is also feasible that the different volume of BCMA on the cell surface of myeloma patients are simply the product of membrane BCMA shedding differences.…”
Section: Bcma: a Potential Target In Cancer Treatmentmentioning
confidence: 99%